Dietary inclusion of Moringa oleifera leaf extracts as alternatives to antibiotic growth promoter on live performance, carcass traits, physical meat quality, and health status of broiler chickens - Al Ibne Rifat; Chondhon Chandro Bormon; Md Golam Akib; Mohammad Shamsul Ataher; Md Kamruzzaman; Amitush Dutta; Amio Kante Das; Kanan Talukder; Mahmoud Azzam; Mohammed Hamdy Farouk; Razib Das; Shad Mahfuz (Italian Journal of Animal Science)
This study investigated the effects of Moringa oleifera leaf extracts (MLE) in broiler diets on growth performance, carcass characteristics, physical meat quality, haematological parameters, and caecal bacterial counts. A total of 144 Arbour Acres broilers were randomly assigned into 3 experimental groups (eight replicates having six chicks), naming control (received a basal diet with fresh drinking water), antibiotic (75 mg chlortetracycline/L of drinking water), and MLE (50 ml Moringa oleifera leaf extracts/L of drinking water). The MLE group had the highest average daily gain, final body weight, and lower feed conversion ratio than both control and antibiotic groups. Overall, the MLE treatment significantly reduced (p < 0.05) the broiler’s feed consumption. Although, MLE lowered abdominal fat, other visceral organ and carcass traits showed no variations. The pH value of the breast muscle at 24 h in the MLE group was higher compared to the control and antibiotic groups. Additionally, the cooking loss % and drip loss % at 24 h and on day 7 were the lowest in the MLE group. The haemoglobin and red blood cell levels were significantly higher (p < 0.05), and total cholesterol and triglyceride levels were significantly lower in the MLE group than the control and antibiotic groups. Broilers in the MLE group had lower E. coli as well as total aerobic counts compared to the control-fed group. In conclusion, MLE at 50 mL/L of drinking water can be a potential alternative to antibiotic growth promoters for enhancing broilers’ growth, health and meat quality.